Analisis Partisipasi Masyarakat Dalam Pelaksanaan Pembangunan Desa Untuk Mengoptimalkan Kesejahteraan Masyarakat Di Desa Bandar Klippa, Kecamatan Percut Sei Tuan, Kabupaten Deli Serdang - maringan panjaitan; Evi Phaninora Pandiangan (LPPM Universitas HKBP Nommensen, 2022)
The role of participation in the implementation of village development is a very important component for the success of the village development program. So that community participation can run optimally. Therefore, the village government should play an active role in developing community participation in the implementation of development programs. The purpose of this study is to find out how community participation in the implementation of village development is to optimize community welfare. This study uses a qualitative descriptive research method using interview and observation techniques. This study uses